IMPROVING READING COMPREHENSION SKILL THROUGH LANGUAGE GAMES AT VII GRADE OF JUNIOR HIGH SCHOOL - Yulandari, Evi Safitri; Widiati, Bidarita; Januardi, Dedi; Sukisno, Sukisno (LPPM Institut Pendidikan Nusantara Global, 2022)
This research is aimed at improving the students’ reading comprehension at grade seven of SMP Negri 4 Praya in the academic year of 2022/2023. The teaching reading skill of seven grade students of SMP Negri 4 Praya was through language games. To achieve the objective, collaborative work involving the researcher, the English teacher, the principal, and the students of grade seven was conducted. This study was action research study consisting of two cycles. The steps of the research were: planning, action observation, and reflection. The data were obtained by observing the teaching and learning process during the implementation of the actions, interviewing the English teacher and the students of seven grade students, and holding discussions with the English teacher. The instruments for gathering the data were a recorder, a camera, and interview guidelines. The data analyses were in the forms of field notes, recordings, interview transcripts, and photographs. The result showed that in Cycle 1 the implementation of language games was successful in improving the students’ reading comprehension and their interest in reading during the teaching and learning process. However, the language games which was implemented through group work was not successful because there were some students who were not actively engaged in the group work. Therefore, the researcher improved that action by applying pair work and giving reward. Meanwhile, it was shown in Cycle II that the implementations of language games were successful in improving the students’ reading comprehension and interest in reading during the teaching learning process. From the two cycles, the implementations of language games were effective to improve students’ reading comprehension.